1995
DOI: 10.1128/mcb.15.9.4661
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Five Replication Factor C Genes of Saccharomyces cerevisiae

Abstract: Replication factor C (RFC) is a five-subunit DNA polymerase accessory protein that functions as a structure-specific, DNA-dependent ATPase. The ATPase function of RFC is activated by proliferating cell nuclear antigen. RFC was originally purified from human cells on the basis of its requirement for simian virus 40 DNA replication in vitro. A functionally homologous protein complex from Saccharomyces cerevisiae, called ScRFC, has been identified. Here we report the cloning, by either peptide sequencing or by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
237
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(242 citation statements)
references
References 65 publications
(86 reference statements)
5
237
0
Order By: Relevance
“…S3 A and B). Because RFC1 is essential for cell growth in yeast (28), this finding indicates the knockdown did not exceed a threshold necessary for normal or near-normal cell growth. After transfection of p8TR DNA (encoding G418 resistance) into BJAB or BJAB/ LANA cells and seeding cells at 1,000, 100, or 10 cells per well in microtiter plates, outgrowth of G418-resistant cell lines was much more robust in BJAB/LANA cells compared with BJAB cells (Fig.…”
Section: Rfc Knockdown Results In Highly Deficient Lana-mediated Episomementioning
confidence: 83%
“…S3 A and B). Because RFC1 is essential for cell growth in yeast (28), this finding indicates the knockdown did not exceed a threshold necessary for normal or near-normal cell growth. After transfection of p8TR DNA (encoding G418 resistance) into BJAB or BJAB/ LANA cells and seeding cells at 1,000, 100, or 10 cells per well in microtiter plates, outgrowth of G418-resistant cell lines was much more robust in BJAB/LANA cells compared with BJAB cells (Fig.…”
Section: Rfc Knockdown Results In Highly Deficient Lana-mediated Episomementioning
confidence: 83%
“…Similarly, RFC5 contains an SRC motif and has a modified ATP binding site sequence suggesting that even if it binds ATP it may not easily hydrolyze it (6). According to the subunit arrangement determined here, RFC5 contributes a catalytic arginine to the ATP site of RFC2.…”
Section: Resultsmentioning
confidence: 99%
“…The five subunits of RFC are each different proteins, but they are homologous to one another (6,7) and are members of the AAAϩ family of ATPases (8). The recent crystal structure of E. coli ␥ complex, the prokaryotic counterpart of RFC, has facilitated detailed hypothesis regarding RFC structure and mechanism (9,10).…”
mentioning
confidence: 99%
“…Sequence analyses revealed that human (h)Ctf18, hDcc1, and hCtf8 contain 975, 393, and 121 amino acids and possess molecular masses of 107, 45, and 14 kDa, respectively. Ctf18 is an RFC-like protein containing the conserved RFC boxes II-V and VII-VIII (30,33). Unlike RFC1, the largest subunit of replicative RFC, Ctf18 lacks the ligase homology domain.…”
Section: Resultsmentioning
confidence: 99%
“…32). All RFC subunits possess sequence similarities [RFC boxes (33)], and four of the five subunits have NTP-binding sites. A second alternative RFC derivative was shown recently to play a role in the DNA-damage replication checkpoint response (34,35).…”
mentioning
confidence: 99%